Apie galvos pavadinimą baltų ir tocharų kalbose - Karaliūnas, Simas (Baltistica, 1970)
ON DENOMINATION OF A HEAD IN THE BALTIC AND TOCHARIAN LANGUAGES The paper aims to reveal a striking parallel between the Baltic and Tocharian languages in denomination of a head: in Baltic as well as in Tocharian lexemes of a head are cognate to those of an end, cf. Lith. galvà, Latv. gal̃va, OPr. galwo, gallū “head” : Lith. gãlas, Latv. gals “end”, OPr. acc. sing. gallan “death” (: Lith. gélti “sting, bite, ache”, Latv. dzel̃t “prick, sting, stitch”) and Toch. В āśee “head” : Toch. B āke, A āk “end” (: IE *aḱ- “sharp, pointed, acute”).